HIV prevention programmes for female sex workers in Andhra Pradesh, India: outputs, cost and efficiency - Someshwar M; Marseille Elliot; Rao M Chalapathi; Kumar A Anod; Ramesh YK; Kumar SG Prem; Sisodia Pratap; Dandona Lalit; Marshall Nell; Kahn James G (BMC, 2005)
Abstract Background Female sex workers and their clients play a prominent role in the HIV epidemic in India. Systematic data on the outputs, cost and efficiency for HIV prevention programmes for female sex workers in India are not readily available to understand programme functioning and guide efficient use of resources. Methods Detailed output and cost data for the 2002-2003 fiscal year were obtained using standardised methods at 15 HIV prevention programmes for female sex worker in the state of Andhra Pradesh in southern India. The services provided and their relation to the total and unit economic costs were analysed using regression techniques. The trends for the number of sex workers provided services by the programmes since inception up to fiscal year 2004-2005 were examined. Results The 15 programmes provided services to 33941 sex workers in fiscal year 2002-2003 (range 803-6379, median 1970). Of the total number of contacts with sex workers, 41.6% were by peer educators and 58.4% by other programme staff. The number of sex worker contacts in a year by peer educators varied 74-fold across programmes as compared with a 2.7-fold variation in sex worker contacts by other programme staff. The annual economic cost of providing services to a sex worker varied 6-fold between programmes from Indian Rupees (INR) 221.8 (US$ 4.58) to INR 1369 (US$ 28.29) with a median of INR 660.9 (US$ 13.66) and mean of INR 517.8 (US$ 10.70). Personnel salaries made up 34.7% of the total cost, and recurrent goods made up 38.4% of which 82.1% was for condoms. The cost per sex worker provided services had a significant inverse relation with the number of sex workers provided services by a programme (p < 0.001, R2 = 0.75; power function). There was no correlation between the full time equivalents of programme staff and the number of sex workers provided services by the programmes, but there was a modest inverse correlation between the number of sex workers served and the average time spent with each sex worker in the year adjusted for the full-time equivalents of programme staff (p = 0.011, R2 = 0.40; exponential function). The average number of sex workers provided services annually by the first batch of 7 programmes started in early 1999 plateaued after the fourth fiscal year to 3500, whereas the 8 second-batch programmes started in late 2000 reached an average of 2000 sex workers in 2004-2005 with an increasing trend up to this fourth fiscal year. Conclusion The HIV prevention efforts in this Indian state would benefit from standardisation of the highly variable services provided by peer educators, who form an important part of the sex worker programmes. The cost per sex worker served decreases with increasing number of sex workers served annually, but this has to be weighed against an associated modest trend of decrease in time spent with each sex worker in some programmes.